Capital account liberalisation - Kasekende, Louis (Willey, 2002)
Following full liberalisation of the capital account in 1997, Uganda realised increasing private capital flows. However, this has posed enormous challenges and risks. Macroeconomic management has been complicated because of the limited range and potency of available instruments. Moreover, not only are the financial institutions exposed to more risk and hence need stronger regulation and supervision, but the private sector also needs to develop instruments to hedge and manage the increasing risks in an open economy. This article argues that policy-makers should strengthen regulations, reporting requirements and data collection systems, and design market-friendly instruments to facilitate more appropriate management of a liberalised economy, while reducing volatility.
: the Ugandan Experience
Keywords: Capital Account; Liberalisation; Uganda